Sharia Fintech: The Collaboration of Information Technology and Morality as A Financing Instrument for The Future - Atikah Nurul Ichsan; Iren Despileny; Nisa Zahratul Jannah; Muhammad Albahi (Yayasan Pendidikan Islam Al-Matani, 2024)
The advancement of technology and knowledge has driven global innovation, transforming social, personal interactions, and economic transactions through the internet. Technology companies such as software, web, and internet play a crucial role in Indonesia's industry, particularly in the innovation of economic transactions known as financial technology (fintech). Meanwhile, Shariah financial systems, based on Shariah principles, offer ethical and just alternatives in financial management, known as Shariah fintech. This study employs literature review methods to examine Shariah fintech as a key instrument in future financing. Research findings indicate that there are currently 7 Shariah fintech P2P lending companies established in Indonesia. Shariah fintech's advantages in financing instruments over conventional methods include unique regulations tailored for Shariah fintech, direct oversight by the Shariah Supervisory Board (DPS), and operations based on Shariah principles. Furthermore, Shariah fintech supports sustainable economic growth by avoiding financing sectors that are prohibited and promoting profit-sharing models. Regulatory support from the government, OJK, and DSN-MUI creates an environment conducive to the development of the Shariah financial industry. Overall, with the world's largest Muslim population, Shariah fintech not only provides Shariah-compliant financing solutions and promotes financial inclusion but also plays a crucial role in supporting sustainable economic growth in Indonesia.